The Lind Lehmer constant for Z(p)(n) - De Silva, Dilum P.; Pinner, Christopher G. (My University, 2014)
We determine the Lind Lehmer constant for groups of the form Z(np).
Keywords: Mahler measure; Lind's Lehmer Problem; Finite abelian groups